Burns, Production Trends - Crum, W. L. (Quarterly Journal of Economics, 1934)
Journal Article Burns, Production Trends Get access W. L. Crum W. L. Crum Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 48, Issue 4, August 1934, Pages 742–748, https://doi.org/10.2307/1883549 Published: 01 August 1934